United States history - Colonization through reconstruction - Davidson, James West; Stoff, Michael B. (Pearson, 2016)
The early Americas and European exploration prehistory-1550 -- European colonization of North America (1500-1750) -- The revolutionary era (1750-1783) -- A Constitution for the United States (1776-present) -- The early republic (1789-1825) -- The age of Jackson and westward expansion (1824-1860) -- Society and culture before the Civil War (1820-1860) -- Sectionalism and Civil War (1820-1865) -- The Reconstruction era (1865-1877) -- United States Constitution -- Primary sources -- Declaration of Independence -- 21st century skills -- Atlas -- Glossary